The Impact of savings in economic growth - THAW, Zin Win (KDI School, 2017)
The present study investigates long-run equilibrium relationship between real economic growth, foreign direct investment, and domestic savings in Myanmar, which has a developing economy. Bounds tests confirm that foreign direct investments and domestic savings are in long-term equilibrium relationship with real GDP growth. Domestic savings and FDI have positive, statistically significant, and inelastic impact on real GDP both in the long term and short term of the Myanmar economy. Error correction model reveals that real GDP of Myanmar converges to its long-term equilibrium level by 74.7% (which is high) by the contribution of foreign direct investment and domestic savings. Furthermore, domestic savings and foreign direct investments are driven in the long term of the Myanmar economy.
Thesis(Master) --KDI School:Master of Public Policy,2017